The winner gives it all: Unions, tax competition and offshoring - Hyun-Ju Koh; Ferdinand Mittermaier (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2009)
This paper analyzes competition for capital between welfare-maximizing gov- ernments in a framework with agglomeration tendencies and asymmetric union- ization. We find that a unionized country's government finds it optimal to use tax policy to induce industry to relocate towards a location with a competitive labor market instead of realizing the benefits from higher wage income while exporting part of the wage burden to foreign consumers. Via the tax regime effect, which favors the factor capital, and the efficiency effect, consumers and producers alike benefit from off-shoring industry towards a low-cost country. Our result qualifies first intuition that defending high wage industries is beneficial to a country as part of the associated cost is shifted to foreign consumers.
Keywords: F12; F16; F21; H25; H73; J51; 330; tax competition; trade unions; agglomeration